2021
DOI: 10.1007/s40999-021-00655-3
|View full text |Cite
|
Sign up to set email alerts
|

On Seismic Response Reduction of Adjacent Frame: Emphasis on the Different Characteristics of Earthquakes

Abstract: Seismic response reduction of adjacent frames with the use of dampers, base isolations, or hybrid controls has been considered in recent years. What makes this to be highly important are the different properties of input earthquake loadings that can lead to different results. In this study, friction dampers and LRB isolators were used as the passive energy absorbers and, accordingly, the performance of such devices subjected to a wide range of earthquake loadings has been studied. Two experimental samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The in uence of different characteristics of earthquakes on the seismic response of moment frames in which friction dampers and isolators were used, was evaluated. This research showed that a combination of devices is the most effective way to reduce the inter-story drifts [6]. The economic aspects of using low-damage systems and dampers were also researched by comparing three different types of systems in structures considering the probability of needing to demolish a building after undergoing large residual deformations.…”
Section: Introductionmentioning
confidence: 99%
“…The in uence of different characteristics of earthquakes on the seismic response of moment frames in which friction dampers and isolators were used, was evaluated. This research showed that a combination of devices is the most effective way to reduce the inter-story drifts [6]. The economic aspects of using low-damage systems and dampers were also researched by comparing three different types of systems in structures considering the probability of needing to demolish a building after undergoing large residual deformations.…”
Section: Introductionmentioning
confidence: 99%
“…The structure used was subjected to three sets of NFs, with pulse, NF, and FF records. The analysis results showed that the hybrid control strategy was the most efficient technique for NF with pulse, NF, and FF records [30]. A mega-sub isolation system's seismic response to NF ground motions with velocity pulses were evaluated by Li et al [31].…”
mentioning
confidence: 99%